2023
DOI: 10.26522/brocked.v32i1.962
|View full text |Cite
|
Sign up to set email alerts
|

Partnership Research with Indigenous Communities: Fostering Community Engagement and Relational Accountability

Abstract: Drawing from principles of ethical research we derived from our review of national and international policy documents, in this paper we reflect on our research experiences working in partnership with Indigenous educators in a project to support young Indigenous children’s oral and written language development through collaborative action research. Then, acting on lessons learned from this first partnership project, we describe our efforts to attend to these ethical research principles in a second partnership p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the context of evaluations or research praxis, this has been suggested to be actions guided by transparent consultation, principles (i.e. researcher responsibility), confidentiality, respect for and recognition of rights, consent, safety, collaboration, reflection and mutual benefits (Brant et al, 2023; Fredericks et al, 2011; Herman, 2018; Muller, 2007; Sherwood, 2010; Sherwood & Edwards, 2006; Smith, 2008; Tunón et al, 2016). Evaluative research with the consent of the community and individuals who participate aligns with Indigenous epistemologies and the political realities of Indigenous lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of evaluations or research praxis, this has been suggested to be actions guided by transparent consultation, principles (i.e. researcher responsibility), confidentiality, respect for and recognition of rights, consent, safety, collaboration, reflection and mutual benefits (Brant et al, 2023; Fredericks et al, 2011; Herman, 2018; Muller, 2007; Sherwood, 2010; Sherwood & Edwards, 2006; Smith, 2008; Tunón et al, 2016). Evaluative research with the consent of the community and individuals who participate aligns with Indigenous epistemologies and the political realities of Indigenous lives.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluative research with the consent of the community and individuals who participate aligns with Indigenous epistemologies and the political realities of Indigenous lives. This approach also respects social and communal knowledge as well as individual knowledge, making it consistent (Brant et al, 2023; Cajete, 2017; Chilisa, 2012; Rigney, 1999). Put simply, it is the evaluations that honour the principles of conducting research with and for Indigenous peoples and which move away from the harmful and unethical practices of the past, where the word ‘research’ became ‘one of the dirtiest words in the Indigenous world’s vocabulary’ (Smith, 2021, p. 1).…”
Section: Introductionmentioning
confidence: 99%